Animality and humanity in French late modern representations of black femininity - Silberstein, Elodie, author.
1 online resource
Keywords: "This volume examines the evolution of the depictions of black femininity in French visual culture as a prism through which to understand the Global North's destructive relationship with the natural world. Drawing on a broad spectrum of archives extending back to the late 18th century - paintings, fashion plates, prints, photographs, and films - this study traces the intricate ways a patriarchal imperialism and a global capitalism have paired black women with the realm of nature to justify the exploitation both of people and of ecosystems. These dehumanizing and speciesist strategies of subjugation have perpetuated interlocking patterns of social injustice and environmental depletion that constitute the most salient challenges facing humankind today. Through a novel approach that merges visual studies, critical race theory, and animal studies, this interdisciplinary investigation historicizes the evolution of the boundaries between human and non-human animals during the modern period. The book will be of interest to scholars working in art history, visual studies, critical race theory, colonial and post-colonial studies, animal studies, and French studies"--